Study of Words and Syntactic Structure of SiavashKasrai's Poems - mohammad shokraei (مطالعات زبانی و بلاغی)
The aim of this article is to investigate the words and syntactic structure in Siavash Kasrai's poems. Certainly, one of the most important aspects of poetry analysis for any literary researcher is to examine the poet's ability to take advantage of linguistic possibilities. Undoubtedly, one of the most prominent features of contemporary poetry is the poet's courage in using new words and using various syntactic structures. The studied poet, Siavash Kasraei, can be considered one of the successful followers of Nima Yoshij. The person who has used most of the linguistic possibilities and the variety of words and the use of old and new syntactic structures are the linguistic features of his poetry. Kasraee's attention to colloquial language words, along with the use of old vocabulary, did not cause the poetic and artistic creativity in his poems to decline. Regardless of the very small language slips, in general, the language of Kasra'i's poetry is a coherent and fluent language that often has a social color and smell. In this research, using descriptive-analytical method, we seek to study words and syntactic construction in the poetry of this poet.